Basketball Dribble in Students of SMA Negeri 9 Makassar (Correlation of Arm Muscle Strength, Speed and Agility) - Sahabuddin, Sahabuddin; Hakim, Hikmad; Ishak, Muhammad (Journal of Physical Education and Sport Pedagogy, 2024)
This research is a descriptive quantitative study which aims to determine the contribution of arm muscle strength, speed and agility to the basketball dribbling ability of class XI students at SMA Negeri 9 Makassar. The population of this study was class XI students of SMA Negeri 9 Makassar with a total sample of 43 people selected using a simple random sampling technique. Based on the results of data analysis, the following results were obtained: (1) The agility level of class XI students at SMA Negeri 9 Makassar was in the "good" category with a percentage of 27.96%, (2) The speed level of the class medium” with a percentage of 27.90%. (3) The level of arm muscle strength of class percentage of 69.76%. (5) There is a simultaneous contribution of arm muscle strength, speed and agility to the basketball dribbling ability of class .1%. With the following contribution percentages, arm muscle strength is 17.82%, speed is 29.80%, and agility is 33.76%, while 18.9% is influenced by other factors.